On The Legacies of Derrida and Deconstruction Today: An Interview with Jean-Michel Rabaté. Issue 1 (May 2021) - Greaney, John
Abstract : In this interview, which took place in Center City in Philadelphia in September 2020, I ask Jean-Michel Rabaté to reflect on his personal and writerly relationship with Jacques Derrida, and to assess the legacies of Derrida and deconstruction across the globe today. In the last five years, Rabaté has published three books (one monograph and two edited volumes) on Derrida: Les Guerres de Derrida (Presses de l'Université de Montréal, 2016), After Derrida (Cambridge University Press, 2018), and Understanding Derrida, Understanding Modernism (Bloomsbury, 2019). In response to this flurry of publications, I ask Rabaté what has prompted his recent and vigorous turn to Derrida and what his intentions were with these books. As we review their organising principles, the central thematic of this discussion is thus concerned with Derrida's relevance to the Humanities and Social Sciences as we enter the third decade of the twenty-first century.